Study design and clinical evidence in mRCC: Can we save axitinib as a first-line therapy? - Iacovelli, Roberto (Landes Bioscience, 2014)
Tyrosine kinase inhibitors are de facto the most commonly used targeted therapies for upfront treatment of metastatic renal cell carcinoma (mRCC). After the first era in which targeted agents were compared with placebo and interferon-α, a new phase has started in recent years characterized by head-to-head trials comparing targeted agents in superiority or non-inferiority trials. Recently, the results a head-to-head phase III trial comparing axitinib to sorafenib as upfront therapy in patients affected by mRCC have been reported. We discuss several critical aspects of this study and the results of our metaanalysis on the activity of axitinib over sorafenib in a larger population with the intent to confirm the superiority of axitinib. Despite this, the definition of primary endpoint remains a central factor in determining the final results of a trial.